(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The increased use of digital devices and integration of information technology has resulted in a rise in the development and implementation of artificial intelligence-based bots. Education sector is no exception and is actively exploiting the capabilities of chatbots for teaching and learning. Delhi University too took a leap forward in this regard by enabling its admission chatbot in the current academic session. Since research in this domain is still in its infancy, the present study was undertaken to provide an understanding of the chatbot quality and effectiveness for academic institutions. Responses obtained from 226 students who had used the admission chatbot were analyzed using the technique of CFA and SEM. The results confirm 13 dimensions of chatbot quality for educational services. Further, the performance of the admission chatbot is found to be above average for all the dimensions, indicating the scope as well as need for improvement in its quality and effectiveness, especially with respect to the dimensions of Personalization, Security, and Information Quality which have been revealed to be exerting a significant impact on the overall experience of the users (i.e., students). The findings thus help in identifying important constituents of chatbot quality and may be used by higher education institutions and Universities to develop and integrate chatbots in teaching and learning activities to yield desired experience for students across different disciplines and courses.